Proteomic and Metabolomic Profiling Reveals Alterations in Boar X and Y Sperm - Jia Cheng; Xu Hao; Weijing Zhang; Chenhao Sun; Xiameng Yuan; Yiding Yang; Wenxian Zeng; Zhendong Zhu (Animals, 2024)
Sex-controlled sperm combined with artificial insemination allows animals to reproduce offspring according to the desired sex, accelerates the process of animal genetics and breeding and promotes the development of animal husbandry. However, the molecular markers for sexual sperm sorting are unusual. To identify the molecular markers of boar sperm sorting, proteomics and metabolomics techniques were applied to analyze the differences in proteins and metabolism between X and Y sperm. Label-free quantitative proteomics identified 254 differentially expressed proteins (DEPs) in the X and Y sperm of boars, including 106 proteins that were highly expressed in X sperm and 148 proteins that were highly expressed in Y sperm. Among the differential proteins, COX6A1, COX1, CYTB, FUT8, GSTK1 and PFK1 were selected as potential biological markers for X and Y sperm sorting. Moreover, 760 metabolites from X and Y sperm were detected. There were 439 positive ion mode metabolites and 321 negative ion mode metabolites identified. The various metabolites were phosphoenolpyruvate, phytosphingosine, L-arginine, N-acetylputrescine, cytidine-5′-diphosphate and deoxyuridine. These metabolites were mainly involved in the TCA cycle, oxidative phosphorylation pathway, glycolysis pathway, lipid metabolism pathway, amino acid metabolism pathway, pentose phosphate pathway and nucleic acid metabolism pathway. The differential proteins and differential metabolites obtained by the combined proteomics and metabolomics analysis were projected simultaneously to the KEGG pathway, and a total of five pathways were enriched, namely oxidative phosphorylation pathway, purine metabolism, unsaturated fatty acid biosynthesis, ABC transporters and peroxisomes. In summary, COX6A1 and CYTB were identified as potential biomarkers for boar X and Y sperm sorting.